Penerimaan Orangtua terhadap Anak Disabilitas: (Perspektif Psikologis dan Implikasi terhadap Kesejahteraan Keluarga) - Dewi Daryati; Sri Mulyeni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Children with disabilities live with one or more conditions, physical, cognitive, sensory, or social, that limit their daily activities. These conditions necessitate specialized care and attention tailored to their specific needs. This study aims to explore how parents come to terms with their child’s condition, the factors that influence this acceptance, and its overall impact on family well-being. The results suggest that parental acceptance is rarely a straightforward process. It involves a complex emotional journey, often moving through stages of denial, anger, bargaining, and depression before reaching a point of acceptance. The speed and depth of this process are heavily influenced by both internal and external factors. Internally, spiritual values, educational background, and effective coping strategies play a vital role. Externally, the presence of social support and access to healthcare services are crucial. When parents embrace their child’s condition with unconditional love and focus on their potential, it significantly enhances the child’s developmental outcomes. Conversely, a lack of acceptance can increase the burden of caregiving and hinder the child’s progress.